Numerical Investigation of Thermophoresis and Activation Energy Effects on Maxwell Nano Fluid Over an Inclined Magnetic Field Applied to a Disk - Dudekula Dastagiri Babu; S. Venkateswarlu; E. Keshava Reddy (East European Journal of Physics, 2023)
Numerical model is conducted to investigate the behavior of an incompressible Maxwell nanofluid model flow on a convectively stretched surface, considering the effects of thermophoresis and an inclined magnetic field. The system, originally formulated as a set of partial differential equations, is transformed into a system of ordinary differential equations using similarity transformations. The resulting equations are solved using the Runge-Kutta-Fehlberg method in conjunction with the shooting technique. The obtained physical parameters from the derived system are presented and discussed through graphical representations. The numerical process is assessed by comparing the results with existing literature under various limiting scenarios, demonstrating a high level of proficiency. The key findings of this study indicate that the velocity field decreases as the fluid parameters increase, while the fluid temperature diminishes accordingly. Additionally, the heat transfer rate decreases with increasing fluid and thermophoresis parameters, but it increases with Biot and Prandtl numbers.